Diversity of Ectomycorrhizal Fungal Communities Associated with Tuber koreanum in Korea - Seok-Yong Park; Ahn-Heum Eom (Mycobiology, 2024)
Ectomycorrhizal fungi (EMF) are crucial for the formation of Tuber fruiting bodies, including the newly discovered T. koreanum, in Korea. This study explores the diversity and distribution of EMF communities associated with T. koreanum across various regions in Korea and assesses the effects of soil physicochemical properties on these communities. Soil analysis indicated that T. koreanum habitats have a lower pH compared to T. melanosporum habitats documented in other studies, with sandy loam texture being optimal for fruiting body development. Nonmetric multidimensional scaling analysis revealed significant positive correlations between the relative abundances of certain EMF genera and exchangeable potassium and calcium. These findings offer valuable insights into the ecological requirements of T. koreanum and support future conservation and cultivation strategies for truffle species in Korea.